External challenges to the economic expansion of emerging markets in the post-COVID 19 and post-COP26 era: - Juan Carlos Moreno-Brid; Lorenzo Nalin; Edgar Pérez-Medina (PSL Quarterly Review, 2023)
The purpose of this study is to assess, from a Balance of Payment Constraint Growth (BPCG) theoretical perspective, current key challenges of developing countries that spring from two broad exogenous factors. These factors are: i) global shocks that affect the world economy, and ii) major economic policy changes in developed countries. The BPCG perspective helps to identify to what extent these challenges are rooted in the developing countries’ vulnerabilities and structural weaknesses linked to their role in international trade and capital markets. To discuss the current uncertain global environment potential implications for developing economies – growing inflation, hawkish monetary policy, cross-border flows redistribution, as well as the geopolitical redefinition of international trade and global value chains, among others - the present work builds a BPCG model for the post-COVID era and applies it to evaluate challenges to growth in six countries: Chile, Colombia, Ghana, India, Mexico, and Turkey.